Smart Villages through Information Technology – Need of Emerging India - Prajapati, Mithlesh; Ambhaikar, Asha (International Journal of Computer Sciences and Engineering, 2025)
Human society is developing with rapid momentum and achieved various successes for making its livelihood better. The civilization is witness for various changes related to it‟s the development through different catalysts like industrial development, green revaluation, science and technology, etc. The present era is augmented on Information and Communication Technology. This technology has proved its potential in various sectors of development in urban and rural landscapes. Urban areas are seems to more inclined to accept and adopt Information and Communication Technology due to advantages of literacy and better infrastructure as compared to rural areas. Due to such suitable situations of urban landscapes good amount of success of this technology is visible in the form of smart cities and better livelihood of residing human beings. But the problems, consequences and opportunities in urban areas are different for effective utilization of Information and Communication Technology for sustainable development of rural masses. The present research article discusses about rural development in developing world for the up-liftment of livelihood of the rural masses and to take a „look ahead‟ at scientific developments and technologies that might be influential over the next 10 -20 years. The driving motivation behind the concept on “Smart Village” is that the technology should acts as a catalyst for development, enabling education and local business opportunities, improving health and welfare, enhancing democratic engagement and overall enhancement of rural village dwellers. The “Smart Village” concept aims to realize its goal through providing policymakers with insightful, bottom–up analyses of the challenges of village development.